MULTIPLE CRITERIA DECISION MAKING (MCDM) FOR QUALITY EDUCATION MANAGEMENT IN HIGHER EDUCATION: SYSTEMATIC REVIEW - AFRIADI, BAMBANG (International Journal of Business, Law, and Education, 2022)
Systematically this article discusses and reviews the results of previous research on the development of quality education management character. The Multiple Criteria Decision Making (MCDM) determination methodology is widely applied in various domains to search for ratings that support the standard character of things to the contrary and determine the most effective alternative. Multi-criterion decision making (MCDM) is a modeling tool and methodology for dealing with complex engineering problems. About this article is how the matching method is carried out by matching and comparing land characteristics with criteria so that one conclusion is obtained and systematic reviews collect secondary data, conduct research studies challenge ideal educational management. In this context, the quality of higher education must be improved and optimized.